Effect of Ward Noise Management Combined with Meditation Training on Stroke Rehabilitation Patients - Xiujuan Zhang; Xiaofang Wang; Ting Liu; Hongwei Ha; Jianxiu Dong; Suhui Ma (Noise and Health)
Objective: To study the value of ward noise management combined with meditation training in stroke rehabilitation patients. Methods: According to the retrospective analysis method, 150 stroke patients hospitalized in the rehabilitation center of a Tangshan Workers’ Hospital from July 2020 to December 2023 were selected as study objects. They were divided into three groups, namely the control group (routine rehabilitation care, n = 50), observation group A (meditation training, n = 50), and observation group B (meditation training and ward noise management, n = 50) according to whether they received ward noise management and meditation training. The general demographic data, Fatigue Severity Scale (FSS), Pittsburgh Sleep Quality Index (PSQI), and the Short Form 36 (SF-36) were collected. Chi-square test and analysis of variance were used to analyse the data. Results: The baseline data of the patients in each group were not statistically significant (P > 0.05). Before treatment, no difference in the FSS, PSQI, SF-36 scores and environmental noise level between the groups (P > 0.05) was observed. After management, the scores of SF-36 in observation group B were higher than those in the control group and observation group A (P < 0.05) except for somatic pain. Other indicators in observation group B were lower than those in the control and observation group A (P < 0.001). Conclusions: Ward noise management and meditation training can effectively reduce patients’ fatigue, significantly reducing ambient noise levels, promoting the improvement of life quality, and improving sleep quality.